Penerapan Model Pembelajaran Make A Match Berbantuan Media Kartu Bergambar terhadap Hasil Belajar Ipa Siswa Kelas V SD Negeri Nawangsasi - alfian nurdin; Satinem Satinem; R. Angga Bagus Kusnanto (Journal of Elementary School (JOES), 2024)
This research aims to analyze the learning outcomes of students through the implementation of the Make a Match learning model using picture cards in fifth-grade students at Nawangsasi Public Elementary School, specifically in the subject of Science. The research method used was a Pre-Experimental Design with a One-Group Pre-test and Post-test pattern. The research population consisted of 25 fifth-grade students at Nawangsasi Public Elementary School, with all students being selected as research samples using a saturated sampling technique. The instrument used was a multiple-choice questionnaire that had been tested for validity and reliability. The results of the research showed a significant improvement in the average learning outcomes of students, from 50.29 to 72.76, with a learning mastery level of 80%. Thus, it can be concluded that the implementation of the Make a Match learning model with the use of picture cards significantly enhances students' learning outcomes, especially in the subject of Science. The findings of this research are expected to provide recommendations for teachers and schools to implement the Make a Match learning model with picture cards, enabling students to better understand the material, ultimately leading to improved learning outcomes. Keywords: Learning Outcomes, Picture Cards, Make a Match.